Problem Sosial Dalam Novel Panji Wirapati: Tumpas Pamungkas Karya Nugroho Widjajanto: Tinjauan Sosiologi Sastra Dan Relevansinya Dengan Pembelajaran Sastra Di Sma - Hasanah, Nunung (2016)
Literature is a form of creative and productive in producing a text that has a sense of aesthetic value and reflecting social reality. This study aims to: 1) describe the structure that builds novel Panji Wirapati: Tumpas Pamungkas Widjajanto Nugroho's work; 2) describe the social problems inherent in the novel Panji Wirapati: Tumpas Pamungkas Widjajanto Nugroho's work with a review of sociology of literature; Pamungkas annihilated Widjajanto Nugroho's work with a review of sociology of literature; and 3) describe the relevance of the results of this study with language learning in high school. The research approach used in this study is a qualitative descriptive approach. The object of research in social problems in a novel is Panji Wirapati: Tumpas Pamungkas Widjajanto Nugroho works published by PT Triad, Solo, 2014, the mold I, 511 pages. The data used in this study is a sentence and paragram that shows the structure and social problems in a novel. In addition, the data in this study a novel learning information about the high school curriculum and information about the novel in the curriculum SBC. Sources of primary data in this study is novel Panji Wirapati: Tumpas Pamungkas Widjajanto Nugroho works published by PT Triad, Solo, 2014, the first mold and the Indonesian curriculum SBC high school. Researchers in this technique watch or analyze the structure and social problems in novel novel Panji Wirapati: Tumpas Pamungkas work Nugroho Widjajanto and information in the curriculum SBC high school, then researchers noted back the data captured in the novel Panji Wirapati: Tumpas Pamungkas work Nugroho Widjajanto and information in the high school curriculum SBC to be analyzed. This study uses a theoretical triangulation to examine the validity of the data. The theoretical triangulation conducted by researchers using more than one theoretical perspective in discussing the issues studied. The technique used to analyze the novel Panji Wirapati in this study using heuristic and hermeneutic reading. Berdasarkan hasil penelitian melalui tinjauan sosiologi sastra, problem sosial yang terdapat dalam novel Panji Wirapati, yaitu problem politik, ekonomi, dan problem kependudukan. Implementasi problem sosial dalam novel Panji Wirapati dalam pembelajaran bahasa Indonesia di SMA didasarkan standar kompetensi membaca yang termuat Kurikulum Tingkat Satuan Pendidikan (KTSP) pelajaran Bahasa Indonesia kelas XI. Problem-problem yang dipertimbangkan dalam pemilihan novel Panji Wirapati antara lain dari sudut kebahasaan, masalah psikologis, latar belakang budaya, dan nilai-nilai pendidikan.